Myofibroblastic sarcoma in breast: a case report and literature review - Deng, Zixi; Xia, Chuan; Li, Yuechong; Luo, Yongchao; Shen, Songjie (Frontiers in Oncology, 2024)
Myofibroblastic sarcoma is a malignancy in which myofibroblasts are the main component, with a very low incidence. In this study, we report a case of low-grade myofibroblastic sarcoma (LGMS) in the breast. After the diagnosis of LGMS, the patient received a mastectomy. The patient showed no relapse or progression during the follow-up time of 3 months following the operation.LGMS in the breast is extremely rare, and the limited experience with its diagnosis and treatment brings obstacles to doctors. Therefore, this report summarizes the preoperative diagnosis, treatment, and prognosis of breast LGMS through a literature review.